Scanning electron microscopy of the interaction between Cryptococcus magnus and Colletotrichum gloeosporioides on papaya fruit - Capdeville, Guy de; Souza Junior, Manoel Teixeira; Santos, Jansen Rodrigo Pereira; Miranda, Simoni Paula; Caetano, Alexandre Rodrigues; Falcão, Rosana; Gomes, Ana Crsitina Menezes Mendes (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to investigate possible modes of action of the yeast Cryptococcus magnus in controlling anthracnose (Colletotrichum gloeosporioides) on post harvested papaya fruits. Scanning electron microscopy was used to analyze the effect of the yeast on inoculations done after harvest. Results showed that C. magnus is able to colonize wound surfaces much faster than the pathogen, outcompeting the later for space and probably for nutrients. In addition, C. magnus produces a flocculent matrix, which affects hyphae integrity. The competition for space and the production of substances that affect hyphae integrity are among the most important modes of action of this yeast.